Graded Dietary Turmeric Levels Improve Growth and Carcass Yield in Broilers : Tingkat Kurkuma dalam Pakan yang Diatur Meningkatkan Pertumbuhan dan Hasil Daging pada Ayam Pedaging - Sameerah H. Amen; H.A Noaman; Zakaria Ahmed Hussein; Qana Hussein Ameen AL-Jabari; Mohammed Hasib Mohammed (Academia Open, 2025)
General Background: The rising concerns over antibiotic resistance and food safety have prompted a global move toward natural alternatives in poultry nutrition. Specific Background: Turmeric (Curcuma longa), known for its antimicrobial, antioxidant, and anti-inflammatory properties, is one such promising phytogenic feed additive. Knowledge Gap: While turmeric's bioactivity is well-documented, the optimal dietary levels for maximizing broiler performance and carcass yield remain uncertain. Aims: This study aimed to evaluate the effects of graded dietary turmeric powder (1.5, 3.0, 6.0, and 9.0 g/kg feed) on growth performance, feed efficiency, and dressing percentage in broiler chickens. Results: Turmeric supplementation significantly improved body weight gain, feed intake, and carcass yield (p ≤ 0.05). The 3.0 g/kg group showed the best feed conversion ratio, while the 9.0 g/kg group achieved the highest weight gain and dressing percentage. Novelty: This study demonstrates a dose-dependent relationship between turmeric levels and broiler productivity, identifying both the threshold for maximum efficiency and the potential drawbacks of excessive supplementation. Implications: Turmeric powder at moderate inclusion levels offers a viable natural growth promoter alternative to antibiotics, contributing to sustainable poultry production and public health safety.Highlight : The addition of turmeric increases body weight and carcass percentage in broilers. A dose of 3 g/kg produces the best feed efficiency (lowest FCR). Turmeric can be a natural alternative to antibiotics in poultry feed. Keywords : Turmeric Powder, Broiler Chickens, Growth Performance, Feed Conversion Ratio, Dressing Percentage